2016
DOI: 10.1016/j.theriogenology.2016.03.031
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of spermatogonial stem cell marker expression in undifferentiated felid spermatogonia

Abstract: Spermatogonial stem cells (SSCs) are distinct in their ability to self-renew, transmit genetic information, and persist throughout the life of an individual. These characteristics make SSCs a useful tool for addressing diverse challenges such as efficient transgenic production in nonrodent, biomedical animal models, or preservation of the male genome for species in which survival of frozen-thawed sperm is low. A requisite first step to access this technology in felids is the establishment of molecular markers.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 52 publications
(51 reference statements)
1
9
1
Order By: Relevance
“…Furthermore, in the mouse and several domestic species, PLZF was expressed in both gonocytes and undifferentiated spermatogonia (Costoya et al., ; Zheng et al., ) and was essential for self‐renewal and maintenance of the stem cell pool (Costoya et al., ). In our study, immunostaining for PLZF in cat sections revealed a similar distribution pattern of positive cells as reported in human (Wu et al., ), mouse (Gassei & Orwig, ; Wu et al., ), bull (Reding et al., ) or cat (Vansandt et al., ) testis. In fact, results for foetal and prepuberal testes were strikingly similar to those observed in other species (Costoya et al., ; Gassei & Orwig, ; Wu et al., ).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Furthermore, in the mouse and several domestic species, PLZF was expressed in both gonocytes and undifferentiated spermatogonia (Costoya et al., ; Zheng et al., ) and was essential for self‐renewal and maintenance of the stem cell pool (Costoya et al., ). In our study, immunostaining for PLZF in cat sections revealed a similar distribution pattern of positive cells as reported in human (Wu et al., ), mouse (Gassei & Orwig, ; Wu et al., ), bull (Reding et al., ) or cat (Vansandt et al., ) testis. In fact, results for foetal and prepuberal testes were strikingly similar to those observed in other species (Costoya et al., ; Gassei & Orwig, ; Wu et al., ).…”
Section: Discussionsupporting
confidence: 90%
“…In fact, results for foetal and prepuberal testes were strikingly similar to those observed in other species (Costoya et al., ; Gassei & Orwig, ; Wu et al., ). However, in adult testis, a higher proportion of cells might have been marked by PLZF herein than in a recent study (Vansandt et al., ). The inability to combine PLZF and DDX4 analysis on the same sections precluded definitive identification of potential stem germ cells.…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…Germline stem cells belong to adult stem cells, and they possess the ability that transmit genetic information from generation to generation [15]. Mammalian male germline stem cells, also know as spermatogonial stem cells (SSCs), were identified in the 1950s [2, 6, 7].…”
Section: Introductionmentioning
confidence: 99%